2013
DOI: 10.1142/s1793812013500193
|View full text |Cite
|
Sign up to set email alerts
|

Inflation in Egypt: Internal or External Driven?

Abstract: This paper investigates whether internal or external factors explain in°ation in Egypt over the period 2003M1-2012M12. Using an autoregressive distributed lag model, results indicate that money supply and global commodity prices a®ect in°ation in the long-run, while important short-run factors are in°ation persistence, exchange rate depreciation and supply side bottlenecks. It is also shown that global commodity prices, especially energy prices, pass-through into headline in°ation in Egypt with a short lag. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…According to the study's findings, there exists a positive short-term association between a positive shock to exchange rate and price levels in Egypt from (1990 -2022), and each 10% rise in the value of the US dollar against the Egyptian pound causes the inflation rate to go up by about 7%, While, In the case of a negative shock to the exchange rate, the results showed an inverse relationship, but it is not statistically significant. This means that a 10% rise in the pound's value against the dollar results to a 3% lower in inflation, which is comparable to what (Hosny, 2013) found as well as the results of a (Youssef, 2024) study, which confirmed that the overall depreciation of the EGP against the dollar caused short-term inflation to rise.…”
Section: Anokwuru and Ekpenyong 2020) Analysis Of The Causes Of Infla...supporting
confidence: 86%
See 1 more Smart Citation
“…According to the study's findings, there exists a positive short-term association between a positive shock to exchange rate and price levels in Egypt from (1990 -2022), and each 10% rise in the value of the US dollar against the Egyptian pound causes the inflation rate to go up by about 7%, While, In the case of a negative shock to the exchange rate, the results showed an inverse relationship, but it is not statistically significant. This means that a 10% rise in the pound's value against the dollar results to a 3% lower in inflation, which is comparable to what (Hosny, 2013) found as well as the results of a (Youssef, 2024) study, which confirmed that the overall depreciation of the EGP against the dollar caused short-term inflation to rise.…”
Section: Anokwuru and Ekpenyong 2020) Analysis Of The Causes Of Infla...supporting
confidence: 86%
“…Considering that Egypt's inflation has been persistently high relative to regional and national norms at comparable phases of development, the importance of achieving this goal increases. (Hosny, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of GDP was found to mitigate rather than increase inflation in the studies of Helmy and El‐Sakka and Ghali. Hosny's (2013) study pinpoints to money supply and global commodity prices as the two main long run factors influencing inflation, while the short run factors comprise the exchange rate depreciation, supply‐side bottlenecks in addition to previous inflation. Sharaf (2015) assesses the link between inflation and inflation uncertainty; while Abdelraouf et al (2021) evaluate the structural determinants of inflation in Egypt versus transitory shocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of GDP was found to mitigate rather than increase inflation in the studies of Helmy and El-Sakka and Ghali. Hosny's (2013) The excessive monetary growth, and a rise in the intensity of relative price variability are important long-run determinants of inflation. Money growth needs to be curbed, and price liberalization needs to be tackled using a holistic long-run plan as opposed to the piecemeal approach.…”
Section: The Literature On Inflation Determinants In Egyptmentioning
confidence: 99%
“…The HP filter for GDP decomposes the real GDP growth into trend and cyclical components (De Jong and Sakarya, 2016). Here, the cyclical component represents the output gap which is the difference between the actual series of real GDP growth and its long-run trend (Hosny, 2013).…”
Section: Model Specification and Datamentioning
confidence: 99%